Synthesis and Spectral Studies of Novel Diazepine Derivatives - Baloda, Usha; K. Saini, Rajendra; P. Dobhal, Mahabeer; C. Joshi, Yogesh (Asian Journal of Chemistry, 2010)
Condensation of various 1,3-diketone derivatives (1a-f) with ethylene diamine and o-phenylene diamine in absolute ethanol led to synthesis of novel 1,4-diazepines and 1,5-benzodiazepine derivatives. Structure of newly synthesized 1,4- diazepine derivative (2a-f) and 1,5-benzodiazepine derivatives (3a-f) were established on the basis spectral studies viz., IR, 1H NMR, 13C NMR.